54.4k views
2 votes
What is f(g(x)) for x > 5?

What is f(g(x)) for x > 5?-example-1
User Dstj
by
5.5k points

2 Answers

5 votes

Answer:


\large\boxed{B.\ 4x^2-41x+105}

Explanation:


f(x)=4x-√(x)\\\\g(x)=(x-5)^2\\\\f(g(x))\to\text{put}\ x=(x-5)^2\ \text{to}\ f(x):\\\\f(g(x))=f\bigg((x-5)^2\bigg)=4(x-5)^2-√((x-5)^2)\\\\\text{use}\\(a-b)^2=a^2-2ab+b^2\\√(x^2)=|x|\\\\f(g(x)=4(x^2-2(x)(5)+5^2)-|x-5|\\\\x>5,\ \text{therefore}\ x-5>0\to|x-5|=x-5\\\\f(g(x))=4(x^2-10x+25)-(x-5)\\\\\text{use the distributive property:}\ a(b+c)=ab+ac\\\\f(g(x))=(4)(x^2)+(4)(-10x)+(4)(25)-x-(-5)\\\\f(g(x))=4x^2-40x+100-x+5\\\\\text{combine like terms}\\\\f(g(x))=4x^2+(-40x-x)+(100+5)\\\\f(g(x))=4x^2-41x+105

User Read
by
5.8k points
1 vote

Answer: Option B


f(g(x)) = 4x^2 -41x + 105

Explanation:

We have 2 functions


f(x) = 4x -√(x)


g(x) = (x-5)^2

We must find
f(g(x))

To find this composite function enter the function g(x) within the function f(x) as follows


f(g(x)) = 4(g(x)) -√((g(x)))


f(g(x)) = 4(x-5)^2 -√((x-5)^2)

By definition
√(a^2) = |a|

So


f(g(x)) = 4(x-5)^2 -|x-5|

Since x is greater than 5 then the expression
(x-5)> 0.

Therefore we can eliminate the absolute value bars


f(g(x)) = 4(x-5)^2 -(x-5)


f(g(x)) = 4(x^2 -10x + 25) -(x-5)


f(g(x)) = 4x^2 -40x + 100 -x+5


f(g(x)) = 4x^2 -41x + 105

User AlBaraa Sh
by
4.8k points